Efficiency of Bank Filtration and Post-Treatment - Ray, Chittaranjan (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Riverbank filtration (RBF) schemes for the production of drinking water are increasingly challenged by new constituents of concern, such as organic micropollutants and pathogens in the source water and hydrological flow variations due to weather extremes. RBF and new technology components are integrated and monitoring and operating regimes are adopted to further optimize water treatment in bank filtration schemes for these new requirements. This Special Issue presents results from the EU project AquaNES "Demonstrating synergies in combined natural and engineered processes for water treatment systems" (www.aquanes.eu). Additionally, papers from other research groups cover the efficiency of bank filtration and post-treatment, advantages and limitations of combining natural and engineered processes, parameter-specific assessment of removal rates during bank filtration, and the design and operation of RBF wells. The feasibility, design, and operation of RBF schemes under specific site conditions are highlighted for sites in the US, India, and South Korea